THE OCCURRENCE OF THE METAXYTHERIUM CUVIERI CHRISTOL IN THE LATE MIOCENE SEDIMENTS OF SITIA, CRETE - Μαρκοπούλου-Διακαντώνη Α.; Λόγος Ε. (Bulletin of the Geological Society of Greece, 2018)
Two Sirenian skulls with their upper jaws coming from the Upper Miocene area of the village Achladia determined as Metaxytherium cuvieri Christol have been studied. This species is known up today from the M. Miocene of France (Cottreau, 1928). One skull of Metaxytherium cuvieri Chritol is found at the locality «Tympana» of Achladia village, within the formation of marls- gray marls, at an height of 170 m ca., while the second one is found in the locality «Kefala» of Achladia village within the formation of the gray marls at an altitude of 196 m c a . Metaxytherium cuvieri Christol is an intermediate type between Dugongs and Recent Lamantins (=Manatees). The occurrence of Metaxytherium cuvieri Christol in the Hellenic area contributes to our knowledge of its geographical and stratigraphical distribution in this eastern region of the Mediterranean basin during the Upper Miocene